PELATIHAN LITERASI KEUANGAN BAGI CALON PEKERJA MIGRAN INDONESIA - Yusuf, Ramayani; Fadilah Fulki, Insan; Nurjanah, Isma; Gunardi , Gunardi; Veranita, Mira (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2024)
Indonesia is one of the countries that sends labor abroad. This is based on several factors, among others: (1) large demand for labor abroad, (2) higher wages offered, (3) job opportunities open abroad and (4) gaining new experience and skills while working abroad. The activities are planned by LTSAPMI, coordinated meetings for the implementation of the activities. Implementation of activities in cooperation with PT Laatansa Transit International and a lecturer from the Polytechnic Pajajaran. This training will be conducted at the office of PT. Laantansa Lintas International, Road Werkudara Raya No. 9 Sunyaragi Kecambi City of Cirebon from 14 – 17 May 2024. The material provided is critical thinking in making decisions, making budgets, planning savings and credit and loans. The financial literacy provided can provide insight and supply to be able to work safely in the country of people. Financial literacy given to equip CPMI how to manage the money they earn while working abroad. It is also a collaboration between government, industry and academia in creating a broader and sustainable impact on economic, social, and environmental development.